ANALISA USAHA KERUPUK KULIT IKAN HIU DI KABUPATEN LOMBOK TIMUR - Adi Adi Sulaiman (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
The Research purposes: 1). To find out a description of the economic feasibility in terms of product market conditions, technical aspects, management aspects, legal aspects, social, economic, and environmental aspects of the shark skin cracker business. 2). To determine the value of the sensitivity rate of Gross B/C and Payback Periods to the variable of changes in production decline and the variable of changes in the increase in production costs in the shark skin cracker business. The research design used exploratory sequential mixed methods with the Break Even Point method. Data collection techniques were carried out by means of interviews, observation and recording. The research area was chosen, namely East Lombok Regency, sampling was purposive sampling with the consideration that there were 15 units of shark skin cracker business centers located in Keruak District, Sakra District, and Pringgabaya District. By taking the number of respondents as many as 15 respondents. The results showed that: 1). Shark skin cracker business based on the criteria of economic feasibility is feasible. 3). Shark skin cracker business is based on sensitivity criteria, sensitive to changes in production costs and not sensitive to changes in production costs. Keywords: Financial, Economic Feasibility, Shark Skin Crackers, and Sensitivity